A Qualitative Approach to Evidence‐Based Entrepreneurship: Theoretical Considerations and an Example Involving Business Clusters. (4th February 2014) - Rauch, Andreas; van, Robert; Hulsink, Willem
<x xml:space="preserve">Abstract</x> Most research in evidence‐based entrepreneurship builds on quantitative designs, which is unfortunate because qualitative studies provide a unique contribution to the domain of entrepreneurship. They look at distinctive phenomena in their specific time period and context in one way or another, and can help generate and test new theories. We, therefore, suggest using a systematic synthesis of case studies to aggregate the findings of qualitative research. Moreover, as a first step, we developed an example to demonstrate how this approach can advance evidence‐based entrepreneurship. Specifically, we synthesized 13 cases to examine how business clusters increase the performance of firms within clusters.